2019
DOI: 10.1097/j.pain.0000000000001679
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent low back pain patients demonstrate facilitated pronociceptive mechanisms when in pain, and impaired antinociceptive mechanisms with and without pain

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research.-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 64 publications
3
37
1
Order By: Relevance
“…Low PPT may be the result of pain and related factors. McPhee ME [49] found that as the duration of pain experienced by patients with LBP increased, their PPT decreased, and the residual pain caused by external stimulation lasted longer. The experiments in the present study showed that transverse abdominal muscle training could reduce the radiation range of waist pain and increase PPT, thus providing new evidence of the effectiveness of core muscle training in treating CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…Low PPT may be the result of pain and related factors. McPhee ME [49] found that as the duration of pain experienced by patients with LBP increased, their PPT decreased, and the residual pain caused by external stimulation lasted longer. The experiments in the present study showed that transverse abdominal muscle training could reduce the radiation range of waist pain and increase PPT, thus providing new evidence of the effectiveness of core muscle training in treating CLBP.…”
Section: Discussionmentioning
confidence: 99%
“…This current study indicates that such a distribution can be reversed in healthy individuals. Reduced efficacy of endogenous pain inhibition, as observed in patients with chronic musculoskeletal pain (Christensen et al., 2020; Gerhardt et al., 2017; McPhee and Graven‐Nielsen, 2019b), is referenced as mechanisms contributing to widespread/multisite pain but not local pain (Gerhardt et al., 2017). However, administering ketamine, an NMDA antagonist, it is possible to reduce the area of pain referral in fibromyalgia patients (Graven‐Nielsen et al., 2000) and healthy controls (Schulte et al., 2003), revealing the central nature of mechanisms underlying pain referral.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, HACS was considered as a static phenomenon with prevalence estimates based on a single assessment. Although reliability was high for HACS assessment methods when reported, recent work has suggested that psychological symptoms associated with the CSI [105], as well as PPT and TS [119], may fluctuate with pain severity. For now, it is still unclear if HACS is a state or a trait.…”
Section: Limitationsmentioning
confidence: 97%